THE SATISFACTION OF CUSTOMER AND THE MODELING OF LOYALTY IN THE INDUSTRY OF FAST-FOOD - Sum Sochenda (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study’s primary goals were to look at the antecedent factors influencing customer satisfaction (service quality, food quality, physical environment quality, price fairness, and brand image) and then evaluate the causality between customer satisfaction and loyalty in the fast-food restaurant segment. In this research, 480 questionnaires were delivered to six brand fast-food restaurant customers in Phnom Penh, Cambodia, using a self-administered questionnaire method and a convenience sampling methodology, leaving 403 (=83.95 percent) of the total sample size viable for this research. The acquired data were then analyzed utilizing the statistical software SPSS 22.0 and AMOS 26 Graphics in accordance with structural equation modeling (SEM) and qualitative approaches. Before conducting SEM, confirmatory factor analysis (CFA) was used to check the data's goodness-of-fit to the model, convergent and discriminant validity, and indicator and composite reliability. It was revealed that except for the service quality and the physical environment quality, brand image was shown to be the most significantly positive antecedent of consumer satisfaction, followed by food quality and pricing fairness. Customer satisfaction then affected the amount of customer loyalty. The study findings made significant advances to current theories and management implications, specifically when assessing success determinants in fast-food restaurants.